Effect of indobufen vs. aspirin on platelet accumulation in patients with stable coronary heart disease after percutaneous coronary intervention: An open-label crossover study - Shi, Qiu-Ping; Luo, Xing-Yu; Zhang, Bin; Wang, Xin-Gang; Zhao, Jing; Xie, Qiu-Fen; Liu, Jia-Hui; Liu, Yao-Kun; Jiang, Jie; Zheng, Bo (Frontiers in Pharmacology, 2022)
Purpose This study compared the effect of indobufen with that of aspirin on platelet function in patients with stable coronary heart disease after percutaneous coronary intervention (PCI). Methods Patients with stable coronary heart disease who had undergone PCI and received dual antiplatelet therapy (aspirin 100 mg + clopidogrel 75 mg once daily) for at least 12 months were allocated to receive indobufen 100 mg twice daily + clopidogrel 75 mg once daily, clopidogrel 75 mg once daily alone, indobufen 100 mg twice daily alone, and aspirin 100 mg once daily alone for 1 month each in an open-label crossover manner. Platelet function was assessed by using the rates of arachidonic acid (AA)-induced platelet aggregation (AA-PAR) and adenosine diphosphate (ADP)-induced platelet aggregation (ADP-PAR) measured by light transmission aggregometry, the platelet reactivity index measured by vasodilator-stimulated phosphoprotein (PRI-VASP), and the plasma and urinary thromboxane B2 (TXB2) concentrations recorded at baseline and during each treatment phase. Results Of 56 patients enrolled, 52 completed the study. The AA-PAR was lower in the indobufen alone group than in the aspirin alone group (5.21% [3.39, 7.98] vs 5.27% [4.06, 6.60], p=0.038); there was no significant between-group difference in the plasma (531.16 pg/mL [203.89, 1035.06] vs 373.93 pg/mL [194.04, 681.71], p=0.251) or urinary (3951.97 pg/mL [2006.95, 6077.01] vs 3610.48 pg/mL [1664.60, 6247.61], p=0.717) TXB2 concentration. When the aspirin + clopidogrel group and indobufen + clopidogrel group were compared, similar results were found for AA-PAR (3.97% [3.05, 5.12] vs 3.83% [3.10, 5.59], p=0.947) and both plasma (849.47 pg/mL [335.96, 1634.54] vs 455.41 pg/mL [212.47, 1489.60], p=0.629) and urinary (4122.97 pg/mL [2044.96, 7459.86] vs 3812.81 pg/mL [1358.95, 6021.07], p=0.165) TXB2 concentrations. ADP-PAR was lower in the clopidogrel alone group than in the indobufen alone group (47.04% ± 16.89 vs 61.7% ± 10.50, p<0.001), as was PRI-VASP (66.53% ± 18.06 vs 77.72% ± 19.87, p=0.002). Conclusions: These findings suggest that indobufen has antiplatelet effects similar to those of aspirin in patients with stable coronary heart disease after PCI, and may be an alternative for patients with aspirin intolerance after coronary stenting.